Kinematic analysis of two ways of performing the back handspring - a case study - Omorczyk, J.; Staszkiewicz, R.; Puszczalowska-Lizis, E. (Science of Gymnastics Journal, 2022)
The aim of the study was to compare selected kinematic variables of the back handspring from a standing position (Bh) with a back handspring performed in the movement sequence: round off - back handspring - backward stretched somersault (R BhS). The study included 4 gymnasts (mean age: 19.5 years). The athletes performed 6 repetitions of Bh and RBhS. All gymnastic elements were recorded on film. The artistic gymnastics judges selected the best Bh and the back handspring in the sequence (RBhS) for each competitor, which were then subjected to kinematic analysis. Based on the phase division of the recorded gymnastic elements, the analysis of the temporal structure of movement, changes in displacements and velocity of the athletes' centre of gravity (CG), as well as changes in the position of their trunk in relation to the ground were analysed. In Bh and RBhS, the competitors' horizontal CG velocity component (vx) decreased from the beginning of the first flight phase until the end of the support phase on the lower limbs. In Bh, the median values (Me) of vx decreased from 1.94m/s to 0.8m/s, and in RBhS, from 4.85m/s to 2.24m/s. In the case of the vertical component of velocity (vy), the highest values of Me for both back handsprings were recorded at the end of the support phase on the lower limbs (for Bh and RBhS: 3.27m/s and 4.79m/s, respectively). Both in Bh and RBhS, the value of CG velocity in the horizontal axis decreased from the beginning of the analysed movement until its completion.